2002
DOI: 10.1074/jbc.m206673200
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin I Is Phosphorylated at Ser603 by p21-activated Kinases (PAKs) in Vitro and in PC12 Cells Stimulated with Bradykinin

Abstract: The function of synapsin I is regulated by phosphorylation of the molecule at multiple sites; among them, the Ser 603 residue (site 3) is considered to be a pivotal site targeted by Ca 2؉ /calmodulin-dependent kinase II (CaMKII). Although phosphorylation of the Ser 603 residue responds to several kinds of stimuli, it is unlikely that many or all of the stimuli activate the CaMKIIinvolved pathway. Among the several stimulants tested in PC12 cells, bradykinin evoked the phosphorylation of Ser 603 without inducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 47 publications
(64 reference statements)
2
14
0
Order By: Relevance
“…Our results are consistent with a report that GSIS in MIN6 cells is markedly inhibited by both PD98059 and siRNA-mediated knockdown of ERK1 and ERK2 (Longuet et al, 2005). Furthermore, Longuet et al found that ERK stimulation of insulin secretion is mediated by a mechanism that involves phosphorylation of synapsin I. Synapsin I is also phosphorylated by p21-activated kinases in a CDC42-dependent manner in response to bradykinin receptor stimulation (Sakurada et al, 2002). CDC42 is a small Rho family GTPase that is required for second-phase GSIS (Wang et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with a report that GSIS in MIN6 cells is markedly inhibited by both PD98059 and siRNA-mediated knockdown of ERK1 and ERK2 (Longuet et al, 2005). Furthermore, Longuet et al found that ERK stimulation of insulin secretion is mediated by a mechanism that involves phosphorylation of synapsin I. Synapsin I is also phosphorylated by p21-activated kinases in a CDC42-dependent manner in response to bradykinin receptor stimulation (Sakurada et al, 2002). CDC42 is a small Rho family GTPase that is required for second-phase GSIS (Wang et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…These data indicate that phosphorylation of synapsin domain A is essential for the synapsin-induced enhancement of neurotransmitter release and suggest that endogenous kinases phosphorylating this domain play a central role in the regulation of the efficiency of the exocytotic machinery. al., 1993;Jovanovic et al, 2000;Sakurada et al, 2002), but their presence varies in the different isoforms and orthologues.…”
mentioning
confidence: 99%
“…9C after prolonged exposure. ) The protein kinases PAK, PKA, and CaM kinase II all phosphorylate Ser 9 in vivo in response to multiple regulatory inputs (23,24). The data of Fig.…”
Section: Pak1 and Pka Regulate Gap Inhibition By Phosphorylating Synamentioning
confidence: 83%
“…9B). Phosphorylation at Ser 603 , reported by Sakurada et al (24), was not detected. Phosphorylation by PKA inhibited the regulatory activity of synapsin by 76% and phosphorylation by PAK1 inhibited by 66% (Fig.…”
Section: Pak1 and Pka Regulate Gap Inhibition By Phosphorylating Synamentioning
confidence: 84%
See 1 more Smart Citation